The Impact of Corporate ESG Performance Disclosure across Australian Industries - Amir Gholami; John Sands; Syed Shams (Australasian Accounting, Business and Finance Journal, 2022)
The aims of this study are threefold. Firstly, it examines the long-term improvement in the corporate environmental, social and governance (ESG) performance. Secondly, it highlights the favourable financial implications of the higher corporate ESG performance disclosure. The third aim is to provide insight into the industrial impact on the relationship between corporate ESG performance disclosure and financial performance. This study uses a sample of all Australian publicly listed companies between 2007 and 2017 and conducts a panel regression analysis. It also performs several robustness checks to address the methodological, sample selection and endogeneity issues concerning corporate ESG performance disclosure. The findings show a tangible improvement in Australian companies' corporate ESG performance disclosure, favourably associated with financial performance. However, while the corporate ESG performance disclosure appears to be linked to higher financial performance, this is not the case across different industries. The industrial impact on the association between corporate ESG performance disclosure and financial performance has several implications. Firstly, the stakeholders' pressure on companies to address ESG-related concerns is substantial, enhancing corporate financial performance. Secondly, the findings indicate that corporate ESG performance disclosure does not benefit corporations in different industry sectors equally. It, therefore, requires more focus and interpretation by corporate decision-makers. Thirdly, by promoting ESG-related disclosure, managers should consider diverse stakeholders in different industries that weigh business objectives differently. The results of this study provide insights for corporate managers regarding prioritising resource allocations to ESG-related activities that could impact financial performance differently in different industry sectors. The results of this study contribute to the growing literature on the financial implications of corporate ESG performance disclosures, notably different industrial characteristics.
Keywords: Environmental; Social; Governance; Corporate performance; Industrial sectors